IMMUNOMETABOLIC REGULATION OF BACTERIAL INFECTION, BIOFILMS, AND ANTIBIOTIC SUSCEPTIBILITY - Ying-Tsun Chen; Gaurav Kumar Lohia; Samantha Chen; Sebastián A. Riquelme (Karger Publishers, 2024)
BACKGROUND: Upon infection, mucosal tissues activate a brisk inflammatory response to clear the pathogen: i.e., resistance to disease. Resistance to disease is orchestrated by tissue-resident macrophages, which undergo profound metabolic reprogramming after sensing the pathogen. These metabolically activated macrophages release many inflammatory factors, which promote their bactericidal function. However, in immunocompetent individuals, pathogens like Pseudomonas aeruginosa, Staphylococcus aureus, and Salmonella evade this type of immunity, generating communities that thrive for the long term. SUMMARY: These organisms develop features that render them less susceptible to eradication, such as biofilms and increased tolerance to antibiotics. Furthermore, after antibiotic therapy withdraw, "persister" cells rapidly upsurge, triggering inflammatory relapses that worsen host health. How these pathogens persist in inflamed tissues replete with activated macrophages remains poorly understood. KEY MESSAGES: In this review, we discuss recent findings indicating that the ability of P. aeruginosa, S. aureus, and Salmonella to evolve biofilms and antibiotic tolerance is promoted by the similar metabolic routes that regulate macrophage metabolic reprogramming.